PENDIDIKAN ISLAM DALAM PERSPEKTIF PESANTREN (ANTARA IDEALITA DAN REALITA DI ERA MODERN) - Syaiful Mustofa (Fak. Tarbiyah UIN Maliki Malang, 2012)
Pesantren become one of the magnet which is very draw in conference of concept education of Islam. Pesantren is also expected by most society so can do transformation of knowledge, value, and even character to educative participant to become bookish human being and with character.But, these days natural pesantren of dizziness in the effort study pattern synergize in pesantren with fast speed of modernity, what in this case is quickly it him information current and technology. Leave from pesantren, efforts to improve study pattern and education of Islam in pesantren continue to be developed in order to can walk balanced with modern era which without having to leave spirit, cultural and activity of pesantren.